An Alternative Approach to Delivering Intensive Dialysis in Pregnancy. Issue 5 (September 2016) - Ross, Louise E.; Swift, Pauline A.; Newbold, Sandra M.; Bramham, Kate; Hurley, Anne; Gallagher, Hugh
Pregnancy outcomes in patients with end-stage renal disease (ESRD) on dialysis are improving. Recent literature supports intensive hemodialysis (HD) as the modality of choice during pregnancy in ESRD. We report the successful delivery of a healthy infant at full term in a patient with ESRD by supplementing peritoneal dialysis (PD) with intermittent HD to achieve adequate dialysis intensity.